Receiving and Responding to WhatsApp Official Group Messages Among Employees: An Early Interpretation Analysis - Omar, Nuredayu; Su Mustaffa, Che; Abu Talib, Zuraidah (International Journal of Engineering and Technology, 2018)
The purpose of this article is to provide an initial analysis of the study related to the process of receiving and responding to the WhatsApp official group messages at work. Many previous studies have focused on the usage factors, advantages and disadvantages, as well as the implications of using WhatsApp. But this paper will reveal the interpretation of a small group of employees at Universiti Utara Malaysia of their roles and actions related to WhatsApp official group messages. A total number of five administrative and academic staffs had been involved in this initial study.Â  The results of this initial study will be used to strengthen the interview questions for the next phases of this study - focus groups and in-depth interviews, as well as the development of a questionnaire instrument. This initial study revealed that all Informants have joined at least one WhatsApp official group and have a number of other WhatsApp groups. Three dominant themes emerged and had been interpreted from the data as related to reception and feedback to the WhatsApp messages, namely the reception and message development; the use of appropriate grammar and manners; and the awareness of time value, respect differences, and message impacts to the organization. This study contributes to an understanding of the real situation of the usage of WhatsApp group in an organization where the selected employees are aware that every message they want to share with others may affect their organization.Â Â